THE ROLE OF PUBLIC DIPLOMACY IN INTERNATIONAL RELATIONS IN FULL PROCESS OF GLOBALIZATION - Gurgu, Elena; Cociuban, Aristide Dumitru (Annals of Spiru Haret University. Economic Series, 2016)
The purpose of this article was to highlight the role of public diplomacy in linking countries of the world in the process of economic globalization. Like objectives we intend to emphasize the kinds of powers that plays an important role in public diplomacy and national policies on public diplomacy. The investigations carried out by us so far shows that contemporary international relations recorded, under the impact of globalization, a process of resizing, which leads to the removal of the state monopoly on foreign policy. As a result, a whole range of non-state actors influence the image of a country abroad and information technologies gives them multiple communication mechanisms. In this situation, diplomatic activities must be accompanied by a process of communication, both in its internal and foreign markets.